Progesterone receptor membrane component 1 deficiency attenuates growth while promoting chemosensitivity of human endometrial xenograft tumors. Issue 2 (28th January 2015) - Friel, Anne M.; Zhang, Ling; Pru, Cindy A.; Clark, Nicole C.; McCallum, Melissa L.; Blok, Leen J.; Shioda, Toshi; Peluso, John J.; Rueda, Bo R.; Pru, James K.
Abstract: Endometrial cancer is the leading gynecologic cancer in women in the United States with 52, 630 women predicted to be diagnosed with the disease in 2014. The objective of this study was to determine if progesterone (P4) receptor membrane component 1 (PGRMC1) influenced endometrial cancer cell viability in response to chemotherapy in vitro and in vivo . A lentiviral-based shRNA knockdown approach was used to generate stable PGRMC1-intact and PGRMC1-deplete Ishikawa endometrial cancer cell lines that also lacked expression of the classical progesterone receptor (PGR). Progesterone treatment inhibited mitosis of PGRMC1-intact, but not PGRMC1-deplete cells, suggesting that PGRMC1 mediates the anti-mitotic actions of P4. To test the hypothesis that PGRMC1 attenuates chemotherapy-induced apoptosis, PGRMC1-intact and PGRMC1-deplete cells were treated in vitro with vehicle, P4 (1 µM), doxorubicin (Dox, 2 µg/ml), or P4 + Dox for 48 h. Doxorubicin treatment of PGRMC1-intact cells resulted in a significant increase in cell death; however, co-treatment with P4 significantly attenuated Dox-induced cell death. This response to P4 was lost in PGRMC1-deplete cells. To extend these observations in vivo, a xenograft model was employed where PGRMC1-intact and PGRMC1-deplete endometrial tumors were generated following subcutaneous and intraperitoneal inoculation of immunocompromised NOD/SCID and nude mice, respectively. Tumors derived from PGRMC1-deplete cells grew slower than tumors from PGRMC1-intact cells. Mice harboring endometrial tumors were then given three treatments of vehicle (1:1 cremophor EL: ethanol + 0.9% saline) or chemotherapy [Paclitaxel (15 mg/kg, i.p.) followed after an interval of 30 minutes by CARBO platin (50 mg/kg)] at five day intervals. In response to chemotherapy, tumor volume decreased approximately four-fold more in PGRMC1-deplete tumors when compared with PGRMC1-intact control tumors, suggesting that PGRMC1 promotes tumor cell viability during chemotherapeutic stress. In sum, these in vitro and in vivo findings demonstrate that PGRMC1 plays a prominent role in the growth and chemoresistance of human endometrial tumors.